Accounting Standards for European Non-profits. Reasons and Barriers for a Harmonisation Process. (2nd January 2021) - Lopez-Arceiz, Francisco J.; Bellostas, Ana J.; Moneva, Jose M.
Abstract: Non-profits (NPOs) are one of the key agents in implementing socio-economic policies, financial reporting being relevant for their stakeholders. Different accounting regulations exist in Europe, with no required, common accounting standards to promote these entities' participation in diverse countries and societies. We analyse the current differences among local accounting regulations related to the elaboration of financial reporting for European NPOs. We accomplish this by considering the primary elements that define an accounting system together with accounting regulations to elaborate on these organisations' financial statements, and specific operations related to tangible fixed assets, donations and volunteering. Despite there are pressures to promote an isomorphic behaviour in the European context, our results evidence intense differences among European local regulations for NPOs, with origin in diverse cultural and non-profit traditions.